Dura mater assists 3D printed porous titanium scaffolds in healing rabbit calvarial defects. (March 2023) - Wang, Tong; Yu, Zhou; Song, Yajuan; Yang, Liu; Chen, Lin; Dang, Juanli; Zeng, Xianhui; Guo, Shuzhong; Su, Yingjun; Song, Baoqiang
Abstract: Titanium implants are widely used in treating calvarial defects, and the dura mater exerts regenerative effects on cranial bone regeneration. Three-dimensional (3D) porous titanium scaffolds is advantageous for bone defect repair. This study aims to evaluate the effect of dura on the integration of porous titanium implant and cranial bone. Forty-five adult male New Zealand white rabbits were used to generate cranial defect models; they were randomly divided into 3 groups: calvarial defect with intact dura mater (group Ⅰ), calvarial defect with partially removed dura mater (group Ⅱ), and calvarial defect with isolated and intact dura mater (group Ⅲ). All defects were repaired with porous titanium scaffolds. Micro computed tomography (Micro-CT), three-dimensional (3D) reconstruction, non-decalcified histologic section, and biomechanical examination were used to analyze new bone formation, histological characteristics at 4 and 12 weeks postoperatively. The results showed no implant looseness or infection in any of the groups. Micro-CT revealed a higher bone volume/total volume (BV/TV) and trabecular number (Tb. N) in group Ⅰ than the other groups at weeks 4 and 12 after implantation. Relative to Groups Ⅱ and Ⅲ, the trabecular thickness (Bh.Th) was significantly larger in group Ⅰ at 12 weeks postoperatively ( p < 0.05), while the trabecular separation (Tb. Sp) was smaller in group Ⅰ at weeks 4 and 12 ( p < 0.05 or p < 0.01). Histological analysis showed more newly formed bone and calcification deposition in group Ⅰ than in the other groups ( p < 0.05). Trabecular bone formation was observed under the silicone membrane. The push out force in group Ⅰ was significantly higher than that in the other groups ( p < 0.05). The intact dura mater substantially improved the osteogenesis and osteointegration properties of porous titanium scaffolds. This study provides meaningful implications for improving titanium scaffold osseointegration. Graphical Abstract: ga1